2018
DOI: 10.1111/bju.14124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing of an immediate instillation of mitomycin C after transurethral resection in 941 patients with non‐muscle‐invasive bladder cancer

Abstract: These data do not support the hypothesis that a very early instillation (on the day of TURBT) of mitomycin C decreases the risk of recurrence as compared with an early instillation (1 day after TURBT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Immediate intravesical chemotherapy following TURBT is considered an effective approach to reduce risk of recurrence [ 18 , 19 ], however, the optional timing of intravesical therapy remains unclear [ 20 ]. Because previous reports have shown that tumor cells are firmly implanted within the first few hours after TURBT, intravesical chemotherapy should be administered as early as possible [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immediate intravesical chemotherapy following TURBT is considered an effective approach to reduce risk of recurrence [ 18 , 19 ], however, the optional timing of intravesical therapy remains unclear [ 20 ]. Because previous reports have shown that tumor cells are firmly implanted within the first few hours after TURBT, intravesical chemotherapy should be administered as early as possible [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Độ tuổi trung bình là 55±11,7 (43-92) tuổi, trong đó nhóm tuổi 51-60 tuổi chiếm tỉ lệ cao nhất. Kết quả này cũng tương đồng với nghiên cứu của Lê Đình Khánh với độ tuổi trung bình là 55,18±17,7 nhưng thấp hơn nghiên cứu của Bosschieter J với tuổi mắc bệnh trung bình là 67 tuổi [8], [9]. Như vậy ta thấy rằng nam giới có tỉ lệ mắc bệnh nhiều hơn nữ giới và dường như dân số trong nước mắc bệnh sớm hơn so với thế giới.…”
Section: Bàn Luậnunclassified
“…Although the exact timing was not registered, the study protocol indicated that the immediate instillation had to be administered within 24 hours after transurethral resection of the tumour. Whether an instillation given within the first few hours after transurethral resection is more effective cannot be answered from our data (8). Although several trials have demonstrated the value of an immediate instillation, it seems that the search for a subgroup of patients that will not benefit from an immediate instillation Letter to the Editor An immediate, single instillation of mitomycin C in non-muscle invasive bladder cancer: can we define which patients do and do not benefit?…”
mentioning
confidence: 95%